STRATEGI PENGEMBANGAN KAWASAN WISATA LIKUPANG KABUPATEN MINAHASA UTARA - Joppi ., Lengkong; Lucia C. Mandey; Charles R. Ngangi (Sam Ratulangi University, 2018)
This study aims to evaluate the condition of tourist areas in Likupang, to know the internal factors and external factors Likupang tourist location development and its strategies of development. The type of this research is descriptive qualitative. Selection of sample research used purposive sampling method. The data collections in this research are primary and secondary data. Primary data were collected through interviews, observations and discussions and documentation. The interview was based on the questionnaire. The discussion was conducted by conducting Focus Group Discussion (FGD) Activities. While secondary data collected from various agencies, among others, Central Bureau of Statistics and North Minahasa District Office. Data were analyzed using SWOT analysis and Development Strategy. The result of research shows that the development strategy of Likupang tourism area based on SWOT analysis result lies in position of Quadrant I which is located between external opportunity and internal strength where the result of analysis obtained by total score of IFAS (Internal Strategic Factor Summary Analysis) is 3,498 and EFAS (External Strategic Factor Summary Analysis) is 3,854. The research concludes that Likupang tourism area development strategy can be done by maintaining panorama and sustainability of beach and Marine Park and also trying to complete infrastructure facilities especially the availability of electricity, water and internet network. Further accelerate the construction of new connecting road from the airport to Likupang so as to shorten the distance and travel time and also set up tourist information center for tourists.